Find the locus of the middle points of the chords for the parabola${y^2} = 4x$ , chord which touches the parabola${y^2} + 4bx = 0$;$\left( {b > 0} \right)$
Answer
Verified
513.6k+ views
Hint: Use the slope-point form$\left( {y - y_1} \right) = m\left( {x - x_1} \right)$to find the equation of the tangent and find the chord of contact. Then use the condition that the discriminant is zero at the point of tangency to find the required locus.
The given equation of the parabola is
${y^2} = 4x$ …(1)
We find that$a = 1$
Let P and Q be points on the parabola. PQ is a chord for the parabola ${y^2} = 4x$
Let $M\left( {h,k} \right)$be the midpoint of the chord PQ of the parabola.
At$M\left( {h,k} \right)$, equation (1) becomes
${k^2} = 4ah$
${k^2} - 4ah = 0$ …(2)
Slope Point form to find the equation of a line passing through a point $\left( {x_1,y_1} \right)$ with a slope$m$is written as $\left( {y - y_1} \right) = m\left( {x - x_1} \right)$
We get the slope by differentiating \[{y^2} = 4ax\]with respect to$x$.
So, let us differentiate equation (1) with respect to$x$to find its slope.
$
{y^2} = 4ax \\
2y\dfrac{{dy}}{{dx}} = 4a \\
\dfrac{{dy}}{{dx}} = \dfrac{{2a}}{y} \\
$
$m = \dfrac{{2a}}{{y_1}}$
Equation of tangent to the parabola \[{y^2} = 4ax\] at any point $A\left( {x_1,y_1} \right)$is given by the slope-point form as
$
y - y_1 = m\left( {x - x_1} \right) \\
y - y_1 = \dfrac{{2a}}{{y_1}}\left( {x - x_1} \right) \\
$
$yy_1 - y{1^2} = 2ax - 2ax_1$ …(3)
\[{y^2} = 4ax\]at$A\left( {x_1,y_1} \right)$ is
$y{1^2} = 4ax_1$ …(4)
Substitute (4) in (3),
$
yy_1 - y{1^2} = 2ax - 2ax_1 \\
yy_1 - 4ax_1 = 2ax - 2ax_1 \\
yy_1 = 2a\left( {x + x_1} \right) \\
$
Since, T=0 for the chord of contact, we get the equation for chord of contact as \[yy_1 - 2a\left( {x + x_1} \right) = 0\]
Hence, the equation for chord of contact is
\[yy_1 - 2a\left( {x + x_1} \right) = 0\] …(5)
At$M\left( {h,k} \right)$, equation (5) becomes
$ky - 2ax - 2ah = 0$ …(6)
Equating equations (2) and (6) and putting $a = 1$ we get the equation of the chord PQ.
${k^2} - 4ah = ky - 2ax - 2ah$
${k^2} - 2h = ky - 2x$
$y = k - \dfrac{{2h}}{k} + \dfrac{{2x}}{k}$ …(7)
The chord touches the parabola
${y^2} + 4bx = 0$ …(8)
Put equation (7) in (8)
$
{\left[ {k - \dfrac{{2h}}{k} + \dfrac{{2x}}{k}} \right]^2} + 4bx = 0 \\
{\left[ {\dfrac{{2x}}{k} + \left( {\dfrac{{{k^2} - 2h}}{k}} \right)} \right]^2} + 4bx = 0 \\
\dfrac{{4{x^2}}}{{{k^2}}} + \dfrac{{{{\left( {{k^2} - 2h} \right)}^2}}}{{{k^2}}} + 2\left( {\dfrac{{2x}}{k}} \right)\left( {\dfrac{{{k^2} - 2h}}{k}} \right) + 4bx = 0 \\
\dfrac{1}{{{k^2}}}\left[ {4{x^2} + {k^2} + 4{h^2} - 4{k^2}h + 4x\left( {{k^2} - 2h} \right)} \right] + 4bx = 0 \\
4{x^2} + {k^2} + 4{h^2} - 4{k^2}h + 4x{k^2} - 8xh = - 4bx{k^2} \\
4{x^2} + 4x\left( {{k^2} - 2h} \right) + 4h\left( {h - {k^2}} \right) + {k^2} = - 4bx{k^2} \\
$
$4{x^2} + 4x\left( {{k^2} - 2h + b{k^2}} \right) + \left( {4{h^2} - 4h{k^2} + {k^2}} \right) = 0$ …(9)
Equation (9) is of the form,$A{x^2} + Bx + C = 0$.
$A = 4,B = 4\left( {{k^2} - 2h + b{k^2}} \right),C = 4{h^2} - 4h{k^2} + {k^2}$
The condition for tangency is that the discriminant ${B^2} - 4AC = 0$
Since, the locus of the middle points of the chords for the parabola ${y^2} = 4x$which touches the parabola ${y^2} + 4bx = 0$ is required, we use this condition for tangency.
$
{\left[ {4\left( {{k^2} - 2h + b{k^2}} \right)} \right]^2} = 16\left( {4{h^2} - 4h{k^2} + {k^2}} \right) \\
16\left( {{k^4} + 4{h^2} + {b^2}{k^4} - 4{k^2}h - 4hb{k^2} + 2b{k^4}} \right) = 16\left( {4{h^2} - 4h{k^2} + {k^2}} \right) \\
{k^4}\left( {1 + {b^2} + 2b} \right) - 4hb{k^2} - {k^2} = 0 \\
{k^4}{\left( {1 + b} \right)^2} - {k^2}\left( {4hb + 1} \right) = 0 \\
{k^2}\left[ {{k^2}{{\left( {1 + b} \right)}^2} - \left( {4hb + 1} \right)} \right] = 0 \\
$
${k^2}{\left( {1 + b} \right)^2} - \left( {4hb + 1} \right) = 0$ …(10)
Replacing points $\left( {h,k} \right)$ by $\left( {x,y} \right)$in the equation (10), we get
${y^2}{\left( {1 + b} \right)^2} - \left( {4bx + 1} \right) = 0$is the required locus.
Note: The equation of the chord is found for the first parabola at the midpoint $\left( {h,k} \right)$and since this touches the other parabola, substitute one value in the other to get an equation. From that equation, use the condition for tangency ($D = 0$) to find the required locus, as it just touches the other parabola.
The given equation of the parabola is
${y^2} = 4x$ …(1)
We find that$a = 1$
Let P and Q be points on the parabola. PQ is a chord for the parabola ${y^2} = 4x$
Let $M\left( {h,k} \right)$be the midpoint of the chord PQ of the parabola.
At$M\left( {h,k} \right)$, equation (1) becomes
${k^2} = 4ah$
${k^2} - 4ah = 0$ …(2)
Slope Point form to find the equation of a line passing through a point $\left( {x_1,y_1} \right)$ with a slope$m$is written as $\left( {y - y_1} \right) = m\left( {x - x_1} \right)$
We get the slope by differentiating \[{y^2} = 4ax\]with respect to$x$.
So, let us differentiate equation (1) with respect to$x$to find its slope.
$
{y^2} = 4ax \\
2y\dfrac{{dy}}{{dx}} = 4a \\
\dfrac{{dy}}{{dx}} = \dfrac{{2a}}{y} \\
$
$m = \dfrac{{2a}}{{y_1}}$
Equation of tangent to the parabola \[{y^2} = 4ax\] at any point $A\left( {x_1,y_1} \right)$is given by the slope-point form as
$
y - y_1 = m\left( {x - x_1} \right) \\
y - y_1 = \dfrac{{2a}}{{y_1}}\left( {x - x_1} \right) \\
$
$yy_1 - y{1^2} = 2ax - 2ax_1$ …(3)
\[{y^2} = 4ax\]at$A\left( {x_1,y_1} \right)$ is
$y{1^2} = 4ax_1$ …(4)
Substitute (4) in (3),
$
yy_1 - y{1^2} = 2ax - 2ax_1 \\
yy_1 - 4ax_1 = 2ax - 2ax_1 \\
yy_1 = 2a\left( {x + x_1} \right) \\
$
Since, T=0 for the chord of contact, we get the equation for chord of contact as \[yy_1 - 2a\left( {x + x_1} \right) = 0\]
Hence, the equation for chord of contact is
\[yy_1 - 2a\left( {x + x_1} \right) = 0\] …(5)
At$M\left( {h,k} \right)$, equation (5) becomes
$ky - 2ax - 2ah = 0$ …(6)
Equating equations (2) and (6) and putting $a = 1$ we get the equation of the chord PQ.
${k^2} - 4ah = ky - 2ax - 2ah$
${k^2} - 2h = ky - 2x$
$y = k - \dfrac{{2h}}{k} + \dfrac{{2x}}{k}$ …(7)
The chord touches the parabola
${y^2} + 4bx = 0$ …(8)
Put equation (7) in (8)
$
{\left[ {k - \dfrac{{2h}}{k} + \dfrac{{2x}}{k}} \right]^2} + 4bx = 0 \\
{\left[ {\dfrac{{2x}}{k} + \left( {\dfrac{{{k^2} - 2h}}{k}} \right)} \right]^2} + 4bx = 0 \\
\dfrac{{4{x^2}}}{{{k^2}}} + \dfrac{{{{\left( {{k^2} - 2h} \right)}^2}}}{{{k^2}}} + 2\left( {\dfrac{{2x}}{k}} \right)\left( {\dfrac{{{k^2} - 2h}}{k}} \right) + 4bx = 0 \\
\dfrac{1}{{{k^2}}}\left[ {4{x^2} + {k^2} + 4{h^2} - 4{k^2}h + 4x\left( {{k^2} - 2h} \right)} \right] + 4bx = 0 \\
4{x^2} + {k^2} + 4{h^2} - 4{k^2}h + 4x{k^2} - 8xh = - 4bx{k^2} \\
4{x^2} + 4x\left( {{k^2} - 2h} \right) + 4h\left( {h - {k^2}} \right) + {k^2} = - 4bx{k^2} \\
$
$4{x^2} + 4x\left( {{k^2} - 2h + b{k^2}} \right) + \left( {4{h^2} - 4h{k^2} + {k^2}} \right) = 0$ …(9)
Equation (9) is of the form,$A{x^2} + Bx + C = 0$.
$A = 4,B = 4\left( {{k^2} - 2h + b{k^2}} \right),C = 4{h^2} - 4h{k^2} + {k^2}$
The condition for tangency is that the discriminant ${B^2} - 4AC = 0$
Since, the locus of the middle points of the chords for the parabola ${y^2} = 4x$which touches the parabola ${y^2} + 4bx = 0$ is required, we use this condition for tangency.
$
{\left[ {4\left( {{k^2} - 2h + b{k^2}} \right)} \right]^2} = 16\left( {4{h^2} - 4h{k^2} + {k^2}} \right) \\
16\left( {{k^4} + 4{h^2} + {b^2}{k^4} - 4{k^2}h - 4hb{k^2} + 2b{k^4}} \right) = 16\left( {4{h^2} - 4h{k^2} + {k^2}} \right) \\
{k^4}\left( {1 + {b^2} + 2b} \right) - 4hb{k^2} - {k^2} = 0 \\
{k^4}{\left( {1 + b} \right)^2} - {k^2}\left( {4hb + 1} \right) = 0 \\
{k^2}\left[ {{k^2}{{\left( {1 + b} \right)}^2} - \left( {4hb + 1} \right)} \right] = 0 \\
$
${k^2}{\left( {1 + b} \right)^2} - \left( {4hb + 1} \right) = 0$ …(10)
Replacing points $\left( {h,k} \right)$ by $\left( {x,y} \right)$in the equation (10), we get
${y^2}{\left( {1 + b} \right)^2} - \left( {4bx + 1} \right) = 0$is the required locus.
Note: The equation of the chord is found for the first parabola at the midpoint $\left( {h,k} \right)$and since this touches the other parabola, substitute one value in the other to get an equation. From that equation, use the condition for tangency ($D = 0$) to find the required locus, as it just touches the other parabola.
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE